Impact of Accrual-based Earnings Management on Investment Efficiency of the Companies Listed in Tehran Stock Exchange - Mohammad Namazi (Shahid Bahonar University of Kerman, 2014)
This study investigates whether and how firm investment efficiency is influenced by the accrual-based earnings management. The major purpose of this paper is investigating and analyzing the relationship between proxy of accrual-based earnings management and firm’s excess investments. Prior researches suggest that earnings management leads to increase in excess investments of firms (over-investments or under-investments). In this study, the data from 63 listed companies in the Tehran Stock Exchange in the period of 1378-1388 (1999-2009) was collected. The results indicated that there is a significant relationship between discretionary accruals (as proxy of accrual-based earnings management) and excess investment. This suggests that firm’s investment behavior is influenced by accrual-based earnings management. The results also indicate that there is a significant relationship between discretionary accruals (as independent variable) and firm’s excess investment in the period afterwards